(x+9)+y=10

Simple and best practice solution for (x+9)+y=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+9)+y=10 equation:


Simplifying
(x + 9) + y = 10

Reorder the terms:
(9 + x) + y = 10

Remove parenthesis around (9 + x)
9 + x + y = 10

Solving
9 + x + y = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + x + -9 + y = 10 + -9

Reorder the terms:
9 + -9 + x + y = 10 + -9

Combine like terms: 9 + -9 = 0
0 + x + y = 10 + -9
x + y = 10 + -9

Combine like terms: 10 + -9 = 1
x + y = 1

Add '-1y' to each side of the equation.
x + y + -1y = 1 + -1y

Combine like terms: y + -1y = 0
x + 0 = 1 + -1y
x = 1 + -1y

Simplifying
x = 1 + -1y

See similar equations:

| 7x-(5x-3)+6x=9 | | -15=13(4t-3) | | -(1)(p+17)=5(p-3) | | 3+2x=6x+7 | | 3+2x=4x+7 | | -1(p+17)=5(p-3) | | 3+2x=4x | | 8b+4c=172 | | -1(n-11)=-3 | | x+0.25x=3.75 | | 2.5x+3.7=11.5 | | y^2+5y=36/y^2+5y | | 0.5x-1.5=12.5 | | 8b+4c=171 | | (2x+2)/(1-x)^2=-1 | | (y^2)+(5y)=36/(y^2+5y) | | 7=6(x-4)-5 | | y^4+(10y^3)+(25y^2)=36 | | 4a-9whena=5 | | 31-7x=4 | | y+1/5=2 | | 80-4x=64 | | 3x+11=41 | | 9x-1=6x+26 | | 2(3x+5)=3(2x+3) | | 6x+10=6x+9 | | 3x-5=-99-10x | | -3-3x=4x+9 | | 75-5x=12-8x | | x/3+3=5/6+2 | | x(3x-11)=44 | | ln(y)+(1/3)*ln(x)=c |

Equations solver categories